Myths of deep and high stress mining — reality checks with case histories - Suorineni, FT (Deep Mining 2017: Proceedings of the Eighth International Conference on Deep and High Stress Mining, 2017)
The theme of this conference is ‘deep and high stress mining’. Obviously, mining at depth and in high stress is a current challenge and will continue to be so. Despite the several years of dedication to this subject and its importance, the definition of what is ‘deep’ and ‘high stress’ remains a matter of conjecture. Clear understanding of these terms, are fundamental to the design of excavations to achieve the benefits of the knowledge accumulated on the subject over the years. This paper aims at critically examining conditions that constitute high stress and explores what is ‘depth’ in the mining context. International case histories are used to demonstrate how a misunderstanding of ‘depth’ and ‘high stress’ can result in wrong mine layouts and excavation designs. The paper then provides conditions that constitute high stress and deep mining as a guide to mine layouts and the design of excavations to cope with these conditions.
Keywords: deep mining